2015
DOI: 10.1108/ijdi-09-2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Structural change and economic growth in selected emerging economies

Abstract: Purpose – This paper aims to investigate the relationship between structural change and economic growth for a panel of four developing countries, namely, Malaysia, Nigeria, Turkey and Indonesia over 1960-2010. Design/methodology/approach – The study extent the growth equation by incorporating degree of openness, labour and investment and construct structural change indices – modified Lilien index and the norm of absolute values. It utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A set of studies showed fiscal decentralization has an effect on economic capacity, such as by Pitsvada and LoStracco (2002) and Elmassri et al (2016); yet, different findings are expressed by Ebdon et al (2016); Luehlfing (1996) and Bracci et al (2014), who indicated a non-significant relationship. The next research gap is the impact of fiscal decentralization against public welfare, for which Singh and Mahajan (2015) show significant and positive relationships, whereas Zulkhibri et al (2015); Raimi and Adeleke (2009); Salih (2003) and Doessel and Williams (2014) show contradicting results. This present study aims to fill the gap of previous studies, as well as to comprehensively examine the impact of fiscal decentralization toward good governance, economic capacity, and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…A set of studies showed fiscal decentralization has an effect on economic capacity, such as by Pitsvada and LoStracco (2002) and Elmassri et al (2016); yet, different findings are expressed by Ebdon et al (2016); Luehlfing (1996) and Bracci et al (2014), who indicated a non-significant relationship. The next research gap is the impact of fiscal decentralization against public welfare, for which Singh and Mahajan (2015) show significant and positive relationships, whereas Zulkhibri et al (2015); Raimi and Adeleke (2009); Salih (2003) and Doessel and Williams (2014) show contradicting results. This present study aims to fill the gap of previous studies, as well as to comprehensively examine the impact of fiscal decentralization toward good governance, economic capacity, and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…They found that industrial growth rate is the major cause of increasing economic growth, agriculture has no role while services have a negative effect which supports the Baumol effect. Zulkhibri et al (2015) found a long-run association between the two variables for their selected 5 emerging countries. Opoku and Yan (2018) found industrialization as an important booster of economic growth in African.…”
Section: Empirical Reviewmentioning
confidence: 91%
“…A variety of empirical studies exist that seek validation of the structural change nexus with productivity and growth. However, a concrete conclusion cannot be drawn yet as the literature provides mix results (Zulkhibri et al, 2015;Vu, 2017). For a better comprehension, the study follows Ahson et al (2017) who categorized the literature into two types: one is decomposition methodology and second is regression-based studies.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Economic development, on the other hand, involves upscaling the social framework and systems, which is not limited to education, healthcare, power distribution, and cultural attitudes (Salem Press, 2017;Brinkman, 1995). It also involves moving resources from low to high productivity areas, a process involving a series of structural transformations (Zulkhibri et al, 2015). Though GDP growth alone cannot lead to structural transformation and economic development, economic growth cannot happen before the required infrastructural and institutional structures are in place (Salem Press, 2017;Brinkman, 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 99%